Legislative efforts for rare disease in China - analysis of the legal grounds and call for a regulatory framework - Wang, Chenguang; Li, Dingguo (Journal of Health Law, 2013)
In response to the challenges posed by rare diseases, some developed countries have set up regulatory frameworks since 1980s. Should developing countries follow suit? This article argues that the limited resources of a developing country, although a major factor for carefully considering just distribution of health spending, should not be used as an excuse to reject the need for such a regulatory framework. It provides both policy and legal arguments for establishing such a framework in developing countries. It also reports the recent development of rare disease legislative efforts by local authorities in China, explains the reasons of a new definition of rare diseases adopted, and elaborates the necessary blocks in an integrated rational framework for rare diseases suitable for China.